Flow boiling in inner annulus of horizontal enhanced tubes. (March 2023) - Wu, Junjie; He, Yan; Li, Wei; Dong, Zeguan; Kedzierski, Mark A.; Cao, Yanlong; Ke, Hanbing
Highlights: Flow boiling heat transfer characteristics of R410A in the outside annulus of horizontal enhanced tubes. Effect of surface structure, mass flux and outlet vapor quality on HTC and frictional pressure drop. Correlation with the highest accuracy suitable for the enhanced tubes. Three enhanced tubes with fins, orthogonal rectangular convex platforms, and T-shaped ribs. Abstract: The flow boiling heat transfer characteristics in the inner annulus of a smooth tube and on three double-sided enhanced tubes (E1, E2, E3) were experimentally investigated. The outer surfaces of the E1, E2 and E3 tubes are respectively a fine array of fins, an orthogonal rectangular convex platforms array, and a T-shaped rib array. All three enhanced tubes have an outer diameter of 15.88 mm and internal fins on the inner surface. All tests were done with R410A as the refrigerant at saturation temperature of 279.15 K. Mass fluxes ranged from approximately 53 kg/(m 2 s) to 101 kg/(m 2 s), with inlet vapor quality maintained at 0.2 and outlet vapor quality maintained at 0.4, 0.6, and 0.8, respectively. The results show that when the outlet vapor quality is 0.8, the E1 and E3 tubes exhibit good performance with heat transfer coefficients (HTCs) approximately 2.7 to 3.1 times that of smooth tube. This enhancement mechanism is due to the additional heat transfer surface area of the liquid film thinning effect, increased nucleation sites, and increased turbulence. The heat transfer degradation associated with the E2 tube was surmised to be due to boiling suppression and this degradation will be mitigated when the outlet vapor quality decreases to 0.6 and 0.4. The frictional pressure drops of the three enhanced tubes is approximately the same and favorably correlates with the mass flux and the average vapor quality. In addition, three existing correlations of flow boiling HTC are compared, and a modified correlation suitable for E1, E2 and E3 tubes is proposed.